Creativity and Organisational Innovation: Qualitative Research in Highly Structured Fields - Downes, Rory Alasdiar (2012)
The dominant approach to creativity study and organisational creativity research has been to work from the assumed, “pragmatic stop-gap” (Martin, p.296) definition that creativity is the “production of novel and useful ideas in any domain” (Amabile, 1996, p.1), which has allowed creativity to be understood when it is seen. This is extremely useful in organisational study, where the ‘outcome’ is paramount to a ‘system’ that cannot possibly be expected to function on anything as relatively ambiguous and metaphysical as many psychologists would have one believe creativity qualifies. This definition empowers the system to recognise creativity. The rebuttals of this view, from the perspective of existential humanism, empower the individual however; ultimately suggesting creative thought and cognitive capacities carry the weight and value in defining creativity stressing ‘ability’ and ‘ideas’ as enough to offer an accurate description: “Creativity is the ability to come up with new ideas that are surprising yet intelligible, and also valuable in some way” (Boden 2002, p.95). To gain a full understanding of creativity functioning in organisations however, the ‘individual’ level of analysis cannot be disregarded merely because it’s relative ambiguity may present utility issues. On the contrary, this paper will argue, that organisational study is the ideal sense-making vessel for a multi-level pursuit and can enlighten creativity study, organisational psychology and practical business management. Specifically the research of this paper responds to the need for field studies in real work organisations as identified by Woodman, Sawyer and Griffin (1993).